MEZZANINE ENABLERS IN THE THEATER SHOW CONSTRUCTION - Mudad Ajil Hassan; Antsar Falih Fadous (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The mezzanine is an intellectual product that creates a model capable of creating unity and harmony between the plastic relations created by the system of lines and blocks with the internal and main relations of the movement of the substance , which constitutes a strong pole in the degree of accommodating the full width and that placing forms and contents within the display space is not sufficient to know the transformations taking place in The rhythmic grid of the show The research includes four chapters, the first chapter contains / the research question / lies in the philosophy of the Mezansen and the construction process of the theatrical performance. Relationship , and the aim of the research was to reveal the possibilities of mezzanine in the construction of theatrical performance . The limits of the research were temporal and spatial in the year 16 and , 20 Tunisia . Objective : Presentation of the play Al-Majnun ,written by Gibran Khalil Gibran . In the second chapter, it contains two topics: The first: the philosophy of theatrical performance .The second :shifts of the space-time scale . In the third chapter: the research procedures, it includes the descriptive and analytical research method, the research tools and the analysis of the research sample, one sample play and one play( the Majnun . ) In the fourth chapter came the results, conclusions, recommendations and a list of Arab and foreign sources .